Optimistic Life Reflected In the Style of ErnestHemingway's The Old Man and the Sea - Suswati Setyaningsih, Herlin, Dr. M. Thoyibi, M.S, Dewi Candraningrum, Ph.D (2015)
This study aims at explaining the symbols used in the novel and describing the values of optimistic life reflected in the symbols used in Hemingway's The Old Man and the Sea. This research is classified as a descriptive qualitative method. The primary data source of this study is the novel The Old Man and the Sea by Ernest Hemingway. The collecting data process is note-taking technique. This study is also categorized as library research. Based on the findings and discussion, the researcher draws the conclusions such follows. First, it is found that there are eleven symbols used in this novel, they are classified into Universal symbol which is considered as a symbol whose meaning is long agreed by community because of their experience of this. The selected symbols taken from the novel that the researcher considers as Universal symbol are sea as a symbol of universe, sun as a symbol of happiness, night as a symbol of suffering and lion as a symbol of strength. The second catagory is Individual symbol. The symbol which is categorized as individual symbol is a symbol which is originally created by authors for the moment of work so interpretating it requires greater attention to context, for their meaning comes almost entirely from context. In the novel The Old Man and the Sea the symbols which the researcher considers as individual symbols are the old man as a symbol of someone who has optimistic life, Manolin (the boy) as a symbol of hope, Joe Di Maggio as a symbol of strong desire, harpoon as a symbol of skill, bird as a symbol of help, marlin (great fish) as a symbol of struggle and shark as a symbol of destructor or problem. Second, There are six elements or values which characterize someone as the one who has optimistic life and these ones are reflected in the symbols used in this novel. They are the values of hope, faith, power, struggle, positive thinking and respect. Second, Those symbols reflect the values of optimistic life which is to be the theme of the novel